Teaching fish new tricks: Repeated exposure to a velocity barrier improves passage performance - Rachel MB Crawford; Eleanor M. Gee; Brendan J. Hicks; Katherine A. Corn; Paul A. Franklin (PLoS ONE, 2025)
Instream structures like culverts and dams can impede upstream fish migration, acting as environmental filters that only allow onward migration of individuals that can successfully pass them. Cognition and learning ability may be an important factor in determining if a fish can successfully traverse such structures. This study investigated the effect of repeated exposure on passage performance of juvenile Galaxias maculatus through an experimental raceway. Over five consecutive days, individual fish were subjected to the same high-speed (0.45–0.5 m s-1) conditions within the raceway, and performance on each day was recorded. The proportion of fish successfully passing the barrier increased significantly from 40% on Day 1–63% on Day 5. Time-to-event analysis further revealed that by Day 5, fish successfully passed the barrier at a significantly faster rate compared to Day 1. However, repeated exposure did not significantly improve approach or entry rates into the raceway. Fish length influenced approach rates, but not entry or passage rates. These findings suggest that cognition and spatial memory play a role in improving passage performance through velocity barriers, but other factors such as attraction flows may also play an important role in successful passage outcomes.